If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6.99 + 0.55c = 11.94 Solving 6.99 + 0.55c = 11.94 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6.99' to each side of the equation. 6.99 + -6.99 + 0.55c = 11.94 + -6.99 Combine like terms: 6.99 + -6.99 = 0.00 0.00 + 0.55c = 11.94 + -6.99 0.55c = 11.94 + -6.99 Combine like terms: 11.94 + -6.99 = 4.95 0.55c = 4.95 Divide each side by '0.55'. c = 9 Simplifying c = 9
| 3t-6t=27 | | -4(-5-8n)+5n= | | x=(20-y)-(20-z) | | x+4.2=27.8 | | 79+9x+6x-4=180 | | 6.99+.55=11.94 | | 12x+4+11x+12=90 | | -2x+0=-2x | | c+(-3)=100 | | x+27.3=14.2 | | 3+4+2x-1=18 | | 3+6(8x+3)= | | f(x)=0.08x^3+x^2+x+0.26 | | 2(x-5)-4x=-7 | | 4x-107-12x=125 | | -x-4y=-20 | | 7r^2+2r-5=0 | | 1x+11+8x=20 | | f(m)=m+4 | | -37+x=123 | | 2x+12=-7x-19 | | 3(4+w)=3(w+4) | | f(10)=0.08x^3+x^2+x+0.26 | | 9x-3+5x+8=15x | | -2(1+6x)-3= | | 3x+12=69 | | 11=2(w-2)+2w | | 10b-10=9b | | -5(9p-4)= | | 48n^2-6=-42n | | f^2+g^2=2fg | | -10x+3=-17 |